DISCUSSION AND PRACTICAL ASPECTS ON CONTROL ALLOCATION FOR A MULTI-ROTOR HELICOPTER - G. J. J. Ducard; M.-D. Hua (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2012)
This paper presents practical methods to improve the ﬂight performance of an unmanned multi-rotor helicopter by using an efﬁcient control allocation strategy. The ﬂying vehicle considered is an hexacopter. It is indeed particularly suited for long missions and for carrying a signiﬁcant payload such as all the sensors needed in the context of cartography, photogrammetry, inspection, surveillance and transportation. Moreover, a stable ﬂight is often required for precise data recording during the mission. Therefore, a high performance ﬂight control system is required to operate the UAV. However, the ﬂight performance of a multi-rotor vehicle is tightly dependent on the control allocation strategy that is used to map the virtual control vector v = [T, L, M, N ]T composed of the thrust and the torques in roll, pitch and yaw, respectively, to the propellers' speed. This paper shows that a control allocation strategy based on the classical approach of pseudo-inverse matrix only exploits a limited range of the vehicle capabilities to generate thrust and moments. Thus, in this paper, a novel approach is presented, which is based on a weighted pseudo-inverse matrix method capable of exploiting a much larger domain in v. The proposed control allocation algorithm is designed with explicit laws for fast operation and low computational load, suitable for a small microcontroller with limited ﬂoating-point operation capability.